RNA-based ovarian cancer research from 'a gene to systems biomedicine' perspective - ARĞA, KAZIM YALÇIN (TAYLOR & FRANCIS INC, 2017)
Ovarian cancer remains the leading cause of death from a gynecologic malignancy, and treatment of this disease is harder than any other type of female reproductive cancer. Improvements in the diagnosis and development of novel and effective treatment strategies for complex pathophysiologies, such as ovarian cancer, require a better understanding of disease emergence and mechanisms of progression through systems medicine approaches. RNA-level analyses generate new information that can help in understanding the mechanisms behind disease pathogenesis, to identify new biomarkers and therapeutic targets and in new drug discovery. Whole RNA sequencing and coding and non-coding RNA expression array datasets have shed light on the mechanisms underlying disease progression and have identified mRNAs, miRNAs, and lncRNAs involved in ovarian cancer progression. In addition, the results from these analyses indicate that various signalling pathways and biological processes are associated with ovarian cancer. Here, we present a comprehensive literature review on RNA-based ovarian cancer research and highlight the benefits of integrative approaches within the systems biomedicine concept for future ovarian cancer research. We invite the ovarian cancer and systems biomedicine research fields to join forces to achieve the interdisciplinary caliber and rigor required to find real-life solutions to common, devastating, and complex diseases such as ovarian cancer.Abbreviations: CAF: cancer-associated fibroblasts

COG: Cluster of Orthologous Groups

DEA: disease enrichment analysis

EOC: epithelial ovarian carcinoma

ESCC: oesophageal squamous cell carcinoma

GSI: gamma secretase inhibitor

GO: Gene Ontology

GSEA: gene set enrichment analyzes

HAS: Hungarian Academy of Sciences

lncRNAs: long non-coding RNAs

MAPK/ERK: mitogen-activated protein kinase/extracellular signal-regulated kinases

NGS: next-generation sequencing

ncRNAs: non-coding RNAs

OvC: ovarian cancer

PI3K/Akt/mTOR: phosphatidylinositol-3-kinase/protein kinase B/mammalian target of rapamycin

RT-PCR: real-time polymerase chain reaction

SNP: single nucleotide polymorphism

TF: transcription factor

TGF-: transforming growth factor-
Keywords: Non-coding RNAs; ovarian cancer; systems biomedicine; transcriptome; LONG NONCODING RNA; DIFFERENTIALLY EXPRESSED GENES; PROTEIN-INTERACTION NETWORKS; WNT/BETA-CATENIN PATHWAY; PREDICTS POOR-PROGNOSIS; TRANSCRIPTIONAL REGULATION; CISPLATIN RESISTANCE; MICRORNA REGULATION; THERAPEUTIC TARGET; METABOLIC NETWORK